Positioning and identification technologies : hardware and firmware for next generation positioning and wireless communication system - Law, Choi Look (2008)
This report consists of two major parts: (i) Implementation of a real time GPS/SINS (Global Positioning System/Strapdown Inertial Navigation System) test-bed, and (ii) Implementation of IEEE802.11 a test-bed. The objective of the real time GPS/SINS test-bed is to implement a real time GPS aided Strapdown INS (SINS) system and to analyze its performance. The GPS/SINS loosely coupled integrated system provides error estimates of vehicle position, velocities and attitude angles. Although the Kalman filter states are estimated currently at a rate of 1 Hz, the data rate of SINS is 20 Hz and with higher rates possible. Lan vehicle test results show that the position accuracy of GPS/SINS with a low cost IMU, the MotionPak II IMU, is nearly the same as that of GPS receiver only. With complete loss of GPS signals up to 10 seconds of GPS outages, position error is shown to be less than 10 meters.